608 Environmental change to reduce child injury in low and middle income countries: a systematic review. (1st September 2016) - Bhatta, Santosh; Deave, Toity; Mytton, Julie
Abstract : Background: Injuries sustained in the home are a significant contributor to the burden of death and disabilities among young children especially those living in Low and Middle Income Countries (LMICs). The objective of this review was to identify and evaluate the effectiveness of environmental change interventions to reduce child injuries and injury hazards in the home in LMICs. Methods: Seven electronic databases were searched for randomised controlled trials (RCTs) and controlled before and after (CBA) studies of environmental change interventions designed to reduce child injuries and home hazards and published up to 1 April 2014. Where possible, meta-analysis was conducted using RevMan 5. Results: In total four studies were included in the review. Only one study (CBA) reported child injury and three studies (RCTs) home hazards. In the CBA study, child resistant containers were found effective to reduce the incidence of paraffin ingestion by 47% during the intervention period and by 50% after the intervention. Data from two RCTs pooled in a meta-analysis found that a multifactorial intervention (home inspection, safety education and safety device) significantly reduced the post intervention mean scores in the intervention group for poisoning hazards (Mean Difference (MD) −0.77; 95% CI: −1.36, −0.19) and burn related unsafe practices (MD −0.37; 95% CI: −0.66, −0.09) but not for fall, electrical and paraffin burn hazards. The intervention (home inspection and safety education, not safety device) used in a single RCT significantly reduced the post-intervention mean scores in the intervention group for fall hazards (MD −0.5; 95% CI −0.66, −0.33) but not for ingestion hazards. Conclusions: There is limited evidence to determine if environmental change interventions reduce child injuries but some evidence suggested that they may reduce home hazards. More evidence is needed to determine if altering the physical home environment by removing potential hazards reduces injuries.